Frameworking vocational teachers’ digital competences: An integrative literature review and synthesis - Lahn, Leif Christian; Berntsen, Svanhild Kristine (Nordic Journal of Comparative and International Education (NJCIE), 2023)
Two decades of international research on digital competence of teachers have provided a number of frameworks for empirical studies and curriculum development. However, research publications addressing the needed digital competence of vocational (VET-) teachers are scarce. In this article we ask to what extent leading conceptual frameworks on digital competence are fruitful templates for studying such competences in the case of VET-teachers’ professional development, and what could be alternative conceptual models that fit this professional category. A synthesis is made of relevant literature based on a theoretical platform in vocational didactics and digitalization that highlights the diversity of international VET-systems and the connectivity between work and school. We adopt an integrative literature research approach that combines systematic procedures and supplementary searches in an iterative way. Our descriptive analysis of the literature indicated that the international research on VET-teachers digital competence had in general a narrow focus on technical skills with a lack of perspective on key issues about their digital competences such as connectivity school / work, subject-specificity, and adaptive pedagogy. The articles tended to leave out contextual issues, for example the changing professional work of vocational teachers and background information about the national VET-systems. However, part of the literature pointed to the need for more “grounded” research starting from case-studies and qualitative data / mixed-methods research. Our synthesis of the literature in light of our theoretical framing identified four main topics for further research on VET-teachers’ digital competence that were incorporated in a working model or a “frameworking” that needs to be further developed in order to provide a rich and validated basis for constructing professional programs.